Quality Management of School Education Based on School Principle Leadership Role, Teacher Professionalism, and Community Participation In East Kalimantan - Elbadiansyah, Elbadiansyah; Masyni, Masyni (Educational Studies: Conference Series, 2023)
Speaking of education, the first thing that come accross our minds is “school”. In this case school is a public organization that provides education services for the community in order to improve the quality of individual communities. Therefore, it becomes a natural thing when people demand the availability of “good school” which reflected the effectiveness of school performance concerned. This is where the quality of education management in schools requiring the role of school leadership, teachers’ professionalism, as well as optimal community participation. Grade or more commonly known as quality constitutes the picture of whole characteristic of goods or services that show its capacities in satisfying the needs of the users. With regards to education in schools, the quality of education always refer to the specifications of educational services in accordance with the purpose or benefit of education itself. That is why, it can be said that the success of an educational program organized by a school organization would be very difficult to achieve without the alignment of views between the principal, teachers and the community about the true meaning of education, and how should the educational process in the school is implemented. Therefore, as it should be the school leaders that in this case is the principal, teachers and communities will work together in an integrated way to implement each educational ideals to form the next generation of good quality in terms of knowledge, skills, and attitudes and moral.